KAJIAN ISOTERMI SORPSI AIR DAN FRAKSI AIR TERIKAT KUE PIA KACANG HIJAU ASAL KOTA GORONTALO [Study on Moisture Sorption Isotherm and Bound Water Fractions of Green Beans Taste of Pia Cake from Gorontalo] - Jamaluddin, Jamaluddin; Molenaar, Robert; Tooy, Dedie (Jurnal Ilmu dan Teknologi Pangan, 2015)
The aims of this work were to study the moisture sorption isotherm and find a suitable mathematical model of sorption isotherm of green beans of  Pia cake from Gorontalo. The sortion isotherm curve was determined by conditioning the Pia cake at various water activities (aw) using saturated salt solution at 30 0C. Data of Pia cake water content at equilibrium were then plotted against water activity. The study found that sorption isotherm of green beanstaste Pia cake were sigmoidal in shape and the mathematical model of Hasley was found to be the most appropriate in predicting the sorption isotherm of green beans taste Pia cake tested. Limits of primary, secondary, and tertiary bound water content were found for the green beans taste Pia as 3,69% db (aw = 0,12), 3,69% db – 7,84% db (aw= 0,12 - 0,42), and 7,84% db – 13,30% db(aw= 0,42 - 1)respectively Key words:   Pia cake,  moisture equilibrium content, mathematicalmodelsof sorption isotherm, dan bound water fractions.